Water table control for rice production in Ghana - Owusu-Sekyere, Joshua Danso (Cranfield University, 2005)
An investigation has been undertaken to determine the consequence of using water table control for lowland rice production by growing rice varieties Azucena and IR36 in sand cores under a controlled environment in a series of experiments in which the water table was held at fixed levels. Each experiment had a duration of six weeks and in all, four treatments were used: (a) water table at a depth of 30 cm below the surface, (b) water table at a depth of 15 cm below the surface, (c) saturated sand and (c) flooded sand. Growth under the two water table depths compared favourably with the flooded and saturated conditions, with plants under the water table control treatments in some cases performing better in terms of plant performance than the saturated or flooded. Plant growth parameters measured were: Tiller number, root dry mass, shoot dry mass, rooting depth, total root length and plant height. Other parameters measured are: Solution nitrogen concentration, redox potential, growth medium temperature and pH levels. When IR36 was used the total root length, number of roots and tiller numbers were significantly greater for the plants in the saturated treatment but there were no significant differences in root mass, shoot mass, and shoot length with regards to water depth. When Azucena variety was used, the 15 cm treatment had the highest shoot mass in addition to the highest tiller numbers. In other parameters, the 15 cm treatment did not show a significant difference to the saturated treatment. The 30 cm treatment performed least well in all parameters measured. Plants under the flooded treatment had a significantly greater root dry mass, shoot dry mass and tiller number than the others. The plants grown under 15 cm water table depth had the least root mass. Tiller numbers for the plants under the 30 cm water table depth were greater than those under the 15 cm water table depth. Differences in plant development parameters generally appeared only after the fourth week. The data suggest that irrespective of the water treatment used, plant development trends remain the same indicating that in the first four weeks of rice growth much less water can be used without affecting plant development. Where Azucena and IR36 were both used the data suggest that water table control might be suitable for both varieties of rice. Differences in the amount of nitrogen present were seen to have had an impact on growth. Varying the form of nitrogen applied did not alter growth parameters to any appreciable extent implying that supply of nitrogen is more important than the form of nitrogen used. The effect of root properties and NH4+ transport through the soil on N uptake under different water regimes has been modelled. The model adequately predicted the root length densities required to explain N uptake rates. It is shown that root length densities increase with decreasing moisture content, allowing larger root length densities to compensate for low nutrient transport rates and although diffusion of nutrients increased with increasing moisture levels, nutrient uptake rates did not follow the same pattern. Rooting length densities and transport of nutrients are not shown to limit uptake of nutrients under any of the water treatments imposed. The feasibility of using water table control in the inland valleys of Ghana was also investigated by simulating the depth of the water table required in the dry season of the years 1996 and 1997. A comparison of water use under water table control and flooding irrigation showed that water savings were possible suggesting that water table control is feasible and beneficial in the inland valleys of Ghana.